Kadar HbA1c pada Pasien Wanita Penderita Diabetes Mellitus Tipe 2 di Rsud Dr. Doris Sylvanus Palangka Raya - Fera Sartika; Nurul Hestiani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Laboratory tests recommended by the ADA as a supportive examination for diagnosing DM are Hemoglobin Adult 1C (HbA1c), HbA1c examination can be used as a reference for monitoring diabetes mellitus because HbA1c can provide clearer information about the true condition in people with diabetes mellitus. HbA1c examination is an examination that reflects the average blood glucose level over a period of 2-3 months. The purpose of this study was to determine the description of HbA1c in female patients suffering from type 2 diabetes mellitus in RSUD dr. Sylvanus Palangka Raya. This research was conducted using a cross sectional study method with accidental sampling technique. The sample used in this study was patients suffering from type 2 diabetes mellitus in RSUD dr. Doris Sylvanus Palangka Raya taken by 15 people. Then examined using the boronate affinity method. The results obtained by the HbA1c category were 4 people (26.67%) good, 6 people (40%) medium and 5 people (33.33%) bad.